Perception, Self Efficacy, Students' Career Interest In Taxation: Family Environment As A Moderating - Suyanto, Suyanto; Desinta Azizah Pramesti; Fuadhillah Kirana Putri (Universitas Airlangga, 2024)
The increase in the number of taxpayers followed by a decrease in the number of tax officials in Indonesia is of concern to researchers to test the career interest of accounting students in choosing a career in taxation. Interest is a psychological factor that is formed and developed by influences from within a person (instrinsic) and influences from outside (extrinsic). Instrinsic factors include perception and self-efficacy. While extrinsic factors are in the form of a family environment. Initially, interest centers on the individual, then centers on other people and other objects in the environment. The purpose of this study was to examine the perception, self efficacy, accounting students' interest in a career in taxation: family environment as a moderating variable. This research is quantitative research. The data used is primary data and is obtained by distributing questionnaires online via google form. The population in this study were accounting study program students in 2020, 2021, and 2022 in Indonesia. Sampling using purposive sampling technique with a total of 181 samples. The data analysis method used is mu ltiple linear regression which is processed using IMB SPSS version 25. The results indicate that perception and self efficacy have a significant positive effect on accounting students' interest in a career in taxation. The family environment cannot strengthen the relationship between perception and accounting students' interest in a career in taxation. The family environment weakens self efficacy on accounting students' interest in a career in taxation .